Correlation of body composition with depression level - Nertila Kusari; Daniela Sukova-Stojmanovska; Abdulla Elezi (Kazimierz Wielki University, 2020)
Background:  The purpose of this paper is to determine the impact of body development and composition on the depression level, and to determine which of the morphological and body composition parameters have higher impact on the manifestation of depression in women aged  19 to 30 years. Methods: The study was conducted on the sample of 50 voluntarily selected test subjects. From 83 women presented at the fitness center "Fitnes Center Mall" in the city of Gjakova for the purposes of this study are voluntarily involved 50 women aged 19 to 30 years with an average age of 23.2 years. For the purpose of this paper were applied 11 body composition variables  and one test for measuring depression levels. Results: The obtained results show that the multiple correlation coefficient between the predictor and the criterion system is quite high R = 0.962. This relation shows that the common variability between the two systems is 93% (R Square = 0.926). Predictive variables that has the influence in the manifestation of depression level are: Height of the body body (HEIG) t=2.784; p<0.008, Body weight (WEIG)  t=-2.194; p<0.034,  and Body mass index (BMI) t=2.908; p<0.006. Conclusions: The research results show that Height of the body,  Body weight,  and Body mass index affect in the rate of depression level. Research shows that although mental and physical health are two separate concepts, yet they are still in a strong relationship, physical condition affects in mental state.